IMPLEMENTATION OF PRECIOUS METAL INVESTMENT (MULIA FINANCING ) MARKETING STRATEGIES IN PT. PEGADAIAN SYARIAH INDONESIA - Lailatul Hijrah; Ella Fitria Rahmayani (Jurnal MD, 2021)
The increasing development of Islamic Economics in Indonesia has forced PT Pegadaian Syariah in Indonesia to market other products other than pawn/Rahn products. One of the targets the millennial generation to invest in precious metals, which can be done at PT Pegadaian Syariah with the concept according to Islamic law, with only Rp. 50.000 - people can already have gold savings at PT Pegadaian Syariah for long-term needs. This study aims to determine the implementation of the precious metal marketing strategy that PT Pegadaian Syariah has carried out. Marketing of precious metals is seen from the concept of marketing mix 4P, namely product, price, place (location), and promotion. Before that, they went through several stages first, namely Segmentation, Targeting, and Positioning. The research method used is the descriptive analysis method, and the data collection technique used literature review. Moreover, the results of this study are that the promotion strategy and marketing strategy carried out by PT Pegadaian Syariah in Indonesia has been running well by the concept of the marketing mix. However, further strategy development must be carried out so that the products offered are more evenly distributed.Keywords: Marketing Strategies, Marketing Mix, Segmentation-Targeting-Positioning